2017
DOI: 10.1002/jobm.201700509
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification, and characterization of a novel serine‐esterase from Aspergillus westerdijkiae

Abstract: Esterases hydrolyze water soluble short chain fatty acids esters and are biotechnologically important. A strain of Aspergillus westerdijkiae isolated from cooking oil for recycling was found to secrete an esterase. The best enzyme production (19-24 U/ml of filtrate) culture conditions were stablished. The protein was purified using ammonium sulphate precipitation, dialysis, and a chromatographic step in Sephacryl S-200 HR. The 32 kDa purified protein presented an optimal temperature of 40°C, with a T of 48.95°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Tween-80 has the oleic acid composition in its nature and maintains the enzyme stability. As in literature it was reported that tween-80 helps the enzyme production and fungus growth when directly add into fermentation media (Castro et al, 2018). Addition of β-mercaptoethanol (1-3%v/v), disulfide bond-reducing agents, resulted in the stability of esterase activity, signifying that the enzyme did not have any important disulfide bond.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Tween-80 has the oleic acid composition in its nature and maintains the enzyme stability. As in literature it was reported that tween-80 helps the enzyme production and fungus growth when directly add into fermentation media (Castro et al, 2018). Addition of β-mercaptoethanol (1-3%v/v), disulfide bond-reducing agents, resulted in the stability of esterase activity, signifying that the enzyme did not have any important disulfide bond.…”
Section: Discussionmentioning
confidence: 83%
“…In the existance of anhydrous organic solvent system, esterases catalyze the esterification, transesterification, and interesterification. Moreover, they usually show enantioselective, chemioselective and regioselective properties (Castro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In another study where prb A esterase was isolated from E. cloacae EM, the molecular mass of purified enzyme was found to be 55 kDa [24]. In a recent study, the molecular mass of purified esterase isolated from Aspergillus westerdijkiae was predicted to be 32 kDa [25]. Fig.…”
Section: Enzyme Purificationmentioning
confidence: 99%
“…Las esterasas se pueden producir de manera constitutiva o inducible (Gandolfi et al, 2000) y pueden ser excretadas por bacterias, levaduras u hongos como se muestra en la Tabla 1 donde se observa que Aspergillus westerdijkiae excreta serina esterasa y es considerada como un catalizador potencial ya que usa como sustrato a los ácidos grasos de cadena corta (Fernández-De Castro et al, 2017). Aspergillus fumigatus excreta glucuronoil esterasa la cual es importante para la degradación de la lignocelulosa (Huynh et al, 2018).…”
Section: Producción De Esterasas Por Microorganismos Y Su Aplicaciónunclassified